What patients with lung cancer with comorbidity tell us about interprofessional collaborative care across healthcare sectors: qualitative interview study - Bossert, Jasmin; Forstner, Johanna; Villalobos Bollen, Matthias Americo; Siegle, Anja; Jung, Corinna; Deis, Nicole; Thomas, Michael; Wensing, Michel; Krug, Katja (BMJ open, 2020)
Background Patients with lung cancer with comorbidity often require treatment and care by different health professionals, in different settings and at different points in time during the course of the disease. In order to organise and coordinate healthcare efficiently, effective information exchange and collaboration between all involved care providers are required. The aim of this study was to assess the views of patients with advanced lung cancer with comorbidity regarding coordination of treatment and care across healthcare sectors. - Methods This qualitative study, as part of the main study, The Heidelberg Milestones Communication Approach, used face-to-face guide-based semistructured interviews with patients with advanced lung cancer and their informal caregivers to explore cross-sectoral information exchange and collaboration in Germany. All generated data were audio-recorded, pseudonymised and transcribed verbatim. Data analysis was performed using qualitative content analysis to structure data into themes and subthemes. All data were managed and organised in MAXQDA. - Results In 15 interviews, participants reported that cross-sectoral collaboration functioned well, if treatments occurred as planned. However, treatment gaps were experienced, especially regarding medication and regimen. As a result, participants felt insecure and obliged to take responsibility for the coordination of healthcare. Patients reported to be in favour of an active patient role but felt that healthcare coordination should still be a responsibility of a care provider. A more intensive information exchange, potentially by using an electronic platform, was expected to strengthen cross-sectoral collaboration. - Conclusion Patients with lung cancer are uncertain about their role in the coordination of treatment and care across healthcare sectors. Healthcare providers should be more aware of care recipients’ willingness of taking on a more active role in healthcare coordination. - Trial registration number DRKS00013469.
Gesehen am 24.09.2020